LIPOPROTEIN CHAOS - Sothivadivel, Shaleni (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hypertriglyceridemia pertains to blood triglyceride values greater than 2.0 mmol/L. Familial combined hyperlipidaemia, residual dyslipidaemia in well-controlled Type 2 DM and familial hypoalphalipoproteinemia are common hereditary disorders associated with hypertriglyceridemia. CASE A A 30-year-old female with Type 2 DM, admitted for uncontrolled DM and hypertriglyceridemia, with the following laboratory results: TG of 82.9 mmol/L (0.0-1.7 mmol/L). T Cholesterol (TC) of 14.97 mmol/L (0.0-5.2 mmol/L), non-HDL 14.48 mmol/L, LDL unmeasurable (0.0- 1.95 mmol/L). She was initiated on insulin infusion, with target glucose of 8-10 mmol/L, medium chain TG (MCT) Oil 5 mls TDS, Rosuvastatin 20 mg ON, T. Fenofibrate 145 mg OD, Omega-3 1500 mg TDS. TG level decreased from 82 mmol/L to 2.7 mmol/L within one week and remained low during follow-up. CASE B A 48-year-old male with no comorbidities presented with left-sided weakness and facial asymmetry. He was treated as a case of cerebrovascular accident. He was incidentally noted to have hypertriglyceridemia of 11.5 mmol/L. TCl and LDL of 17.6 mmol/L and 11.7 mmol/L, respectively. Insulin infusion was initiated with fenofibrate 145 mg OD, atorvastatin 80 mg ON and Omega 3 capsules- 1 g 3 times daily. Upon discharge, his TC level was 6.3 mmol/L with TG of 4.8 mmol/L and LDL of 3.4 mmol/L. TG levels were 3.75 mmol/L during his follow-up visit with the same treatment. CASE C A 30-year-old female was diagnosed with hypertriglyceridemia and type 2 diabetes mellitus in the young. On admission, TC was 8.63 mmol/L, TG >12.4 mmol/L, LDL (lipaemic sample), non-HDL 8.11 mmol/L. She was initiated with insulin infusion, T. Fenofibrate 145 mg OD and Omega-3 FFA 2 g TDS. She was co-managed with a dietitian for a low TG diet with the addition of MCT oil of 8 ml BD, reduced to 5 ml BD due to intolerance. TG levels remained >12.4 mmol. After 48 hours, oral niacin 500 mg OD was added. During follow-up, TG level reduced to 3.64 mmol/L, with TC of 3.54 mmol/L and LDL of 0.82 mmol/L. CONCLUSION Management of hypertriglyceridemia is somewhat debatable, with some familial cases requiring plasma exchange. However, in the 3 case reports presented above, management was successful with insulin infusion, omega 3 FFA, MCT oil and statins.